Effectiveness of strategic planning on the performance of small and medium enterprises in Tanzania: A case study of selected SMEs in Ilala municipality - Mori, Grace T (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirements for the award of the degree of Master of Business Administration (Corporate Management) of Mzumbe University